Date Palm (Phoenix dactylifera) Fruits as a Potential Cardioprotective Agent: The Role of Circulating Progenitor Cells - Alhaider, Ibrahim A.; Mohamed, Maged E.; Ahmed, K. K. M.; Kumar, Arun H. S. (Frontiers in Pharmacology, 2017)
phenolic compounds Abstract Context: Date palms, along with their fruits' dietary consumption, possess enormous medicinal and pharmacological activities manifested in their usage in a variety of ailments in the various traditional systems of medicine. In recent years, the identification of progenitor cells in the adult organ-systems has opened an altogether new approach to therapeutics, due to the ability of these cells to repair the damaged cells/tissues. Hence, the concept of developing therapeutics, which can mobilize endogenous progenitor cells, following tissue injury, to enhance tissue repair process is clinically relevant. Objectives: The present study investigates the potential of date of palm fruit extracts in repairing tissue injury following myocardial infarction potentially by mobilizing circulating progenitor cells. Methods: Extracts of four different varieties of date palm fruits common in Saudi Arabia eastern provision were scrutinized for their total flavonoid, total phenolic, in vitro antioxidant capacity as well as their effects on two different rodent myocardial infarction models. Results: High concentrations of phenolic and flavonoid compounds were observed in date palm fruit extracts, which contributed to the promising anti-oxidant activities of these extracts and the observed high protective effect against various induced in vivo myocardial infarction. The extracts showed ability to build up reserves and to mobilize circulating progenitor cells from bone marrow and peripheral circulation to the site of myocardial infraction. Conclusion: Date palm fruit extracts have the potential to mobilize endogenous circulating progenitor cells, which can promote tissue repair following ischemic injury.